Influence of nanofillers on the properties of urea formaldehyde resin and medium density fiberboard - Anuj, Kumar (2013)
Wood based panel is typically a panel manufactured with wood in the form of fibers combined with a thermoset resin, and bonded at an elevated temperature and pressure in a hot press. The density of boards lie in the range of 600-800 kg/m3 are known as Medium Density Fiberboard (MDF). The required pressing time depends on the curing time of thermoset resin (UF resin). The thermal conductivity of wood fibers is low due to which long duration for the complete curing is required. Several methods and heat transfer models were tested to increase the heat transfer for attaining proper cure of the fiber matrix with steam injection, electromagnetic heating, longer pressing time, etc. Further, emission of formaldehyde with the use of resin is observed. To overcome the problem, wood based composite industries have initiated with reduced formaldehyde content in the resin and included formaldehyde scavengers in the manufacture of MDF. These measures decrease the formaldehyde emissions to a certain extent, but adversely affect the mechanical properties of the boards. In the present work three different types of nanofillers such as multiwalled carbon nanotubes (CNTs), aluminum oxide nanoparticles and nanosize activated charcoal were mixed with UF resin and used in the preparation of MDF. The process has improved heat transfer during hot pressing and achieved proper curing due to enhanced thermo physical properties of wood fibers. The influence of the nanofillers on the curing behaviour, cross-link density of UF resin and visco-elasticity properties were investigated using differential scanning calorimetry (DSC) and dynamical mechanical analysis (DMA). To improve the dispersion of nanofillers into UF matrix, high speed mechanical stirring and ultrasonic treatments were used. The CNTs were oxidized with nitric acid and the functional groups formed on its surface improved the dispersion and interaction with UF matrix. The dispersion of nanofillers in UF resin matrix was confirmed with XRD, FESEM, and DMA tests undertaken. The mixing of CNTs and Aluminum oxide with UF resin have reduced the curing time due to enhanced thermal conductivity of MDF matrix. The heat transfer during hot pressing of MDF improved significantly with the addition of CNTs and Al2O3 nanoparticle and activated charcoal did not have effect on heat transfer. The curing rate of UF resin improved with all the three nanofillers, as the activation energy of UF curing decreased by the DSC results. The physical and mechanical properties of MDF have improved significantly with CNTs and Al2O3 nanoparticle. The activated charcoal has significantly decreased the formaldehyde emission of MDF. The RSM models were developed to optimize the use of CNTs in the production of MDF because CNTs has gave the best results in three nanofillers. The regression models were developed with three independent variables (Pressing time; CNTs% and UF %) for two responses IB and MOR. The optimum values for each variable are 238 s pressing time, 3.5% CNTs and 8.18% UF resin with the predicated values for IB 0.71 MPa and 48.78 MPa for MOR